Design of artificial neural network for voice control of pressure control system for the distribution of petroleum products - Mahmoud, Dalia Mahmoud Adam (Arab Journal for Sciences and Research Publishing, 2016)
This paper presents a study to design an artificial neural network for sound control in a pressure control system. Where the power of artificial neural networks has been exploited in the construction of a voice recognition for use within the control system in the pressure of pipes distribution of petroleum products. The paper presented an effective approach in designing the neural network for the best possible design performance.
Keywords: speech recognition; LPC parameters; Kmean algorithm